The atlas of wintering birds in Britain and Ireland - Lack, Peter (Peter C.) (T & AD Poyser, 2011)
This companion volume to The Atlas of Breeding Birds of Britain and Ireland is derived from surveys of birds present in Britain and Ireland during the three winters, 1981/82, 1982/83 and 1983/84. The surveys were organised by the British Trust for Ornithology and the Irish Wildbird Conservancy, as were the earlier breeding birds surveys. The Winter Atlas maps 200 species, 192 of which have full-page two-colour maps faced by a page of text. The texts (written by over 100 specialists) comment on the survey results, the species generally and the distribution and abundance as mapped. In addition t.